Effects of Different Water Seasons on the Residual Characteristics and Ecological Risk of Polycyclic Aromatic Hydrocarbons in Sediments from Changdang Lake, China - Javid Hussain; Zhenhua Zhao; Yong Pang; Liling Xia; Ittehad Hussain; Xin Jiang (Journal of Chemistry)
The sediments’ samples were collected from Changdang Lake for the concentration of fourteen polycyclic aromatic hydrocarbons in March (dry season), June (wet season), and September (temperate season) 2013. The highest average value of ∑PAHs was detected as 295.28 ng/g dw in March, followed by 240.91 ng/g dw in June and 165.81 ng/g dw in September. Source characterization studies based on the analysis of diagnostic ratio (triangular plot method) suggested that the PAHs in sediments from Changdang Lake were mainly from the mixed combustion source of biomass and petroleum, and the origins of PAHs in different sampling sites have a great deal of temporal and spatial variability during different water seasons. Redundancy analysis was applied to identify the impact factors and the possible relationship between PAHs and environmental parameters. The predicted results showed that the main factors impacting PAHs temporal distribution were temperature, dissolved oxygen, pH, and oxidation-reduction potential, while conductivity showed secondary impacts on the PAHs distribution. Risk assessment of PAHs in sediments was carried out based on the US Sediments Quality Guidelines (SQGs). By comparing the present study results with SQGs standard values results showed that the adverse effects are not expected at the present levels of PAHs contamination observed in the sediments from Changdang Lake.